In Vitro Immunomodulatory Effect of R10 Fraction of Garlic on Viability and Production of TNF-? in CD8+ T Cells - Tuba Ghazanfari; Hosein Rashidi; Shohreh Jalaei; Pegah Alijani (پزشکی بالینی ابن سینا, 2014)
Introduction & Objective: -cells, especially CD8+ T lymphocytes are the most important cells in anti-tumor response. Previously R10 fraction of garlic extract was reported as an immuno-modulator which induced an effective cellular immunity and Th1 responses. In this study the in vitro immunomodulatory effect of R10 on CD8+ T cells viability and production of TNF-α were evaluated. Materials & Methods: In this experimental study, using monoclonal antibodies attached to magnetic beads with isolating columns by magnetic bead method, CD8+ T cells from spleen cells of Balb/C mice were isolated. R10 fraction based on molecular weight was prepared using Ultra filtration. MTT assay was used to evaluate cell viability. TNF-α level was meas-ured in the supernatant of culture of CD8+ T cells by ELISA. Obtained data was compared and analyzed using Nonparametric Test and Keraskel & Wanny's Test tests.. Results: The findings indicate that all dilutions of R10 fraction increased cell viability of CD8+ T cells in comparison with the negative control group and in the presence of ConA with dilution of 1:50 of R10 fraction significantly increased cell viability of CD8+ T Cells compared to ConA alone. Secretion of TNF-α significantly increased by all dilutions of R10 fraction. Conclusion: These findings suggest that R10 fraction of garlic can be used as an Immuno-modulator drug candidate for induction of cellular Immunity in tumor therapy.